Effect of malting conditions and quality characteristics of malt and roasted malt extract from 'acha' grains (Digitaria exilis Stapf). - Olusegun, Lasekan; Salva, J. Terezinha; Abbas, Kassim Ali (Wiley, 2010)
BACKGROUND:Considering the importance of malting and roasting on the quality of 'acha' beverages, a study was conducted to find optimum conditions for malting and the production of a high-quality roasted extract that could be used for an 'acha' beverage.RESULTS:The data obtained were analysed using response surface methodology. The results revealed that the most significant (P < 0.05) malting factors that affect the response variables were the linear terms of germination time and drying temperature. However, for the extract production, the linear term of roasting temperature was the most significant (P < 0.05) factor. The quadratic and interaction terms exhibited significant (P < 0.05) effect in all cases apart from the flavour. CONCLUSION:The overall optimum regions were established at 28 h of germination time, 55 degrees C drying temperature and 5.0% moisture content for the malting conditions while for the extract production, a roasting temperature of 210 degrees C, extraction temperature of 70 degrees C and extraction duration of 20 min were established.